Exploratory study of the enablers and challenges of a social entrepreneur : case of Dr Govender in the Gelvandale community, Port Elizabeth, South Africa - Mfeketho, Chuma Nqabase Masechaba (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
Social entrepreneurs seek to create social value in various ways in the community. Notably, they encounter not only enabling factors but also face and attempt to deal with a variety of challenges in their endeavor to start and run social ventures. This academic paper adopts a single case study approach with the aims to explore challenges and attempts to deal with them, as well as enablers, in how Dr Govender sought to create social value within the community of Gelvandale in Port Elizabeth in South Africa. Famhealth Medipark was chosen because it is unique and has been considered as an example of successful social entrepreneurship in Port Elizabeth. In the light of this, there has not been any previous study particularly focusing on its challenges and enablers in adding social value in the community through a multi-disciplinary venture. This research is valuable as it builds our understanding of how social entrepreneurs create social value. This qualitative study uses a single case study to focus on incidents of challenges and enabling factors as experienced, recollected and expressed by Dr Govender as a social entrepreneur. A variety of data, such as interview data collected through sampling incidents in nine in-depth initial and follow-up interviews, documents, audio documentaries and emails, were used. Open coding and constant comparison was used to analyze data and induce themes. Findings depict that Dr Govender as a social entrepreneur was propelled by four enablers: (1) strong enthusiasm to create positive change in others within a community, (2) network to resources, (3) a nurturing world view, and (4) consistent self-sacrifice. Dr Govender also revealed that he faced four types of challenges in setting up and operating Famhealth Medipark (FHM) as a vehicle with the sole purpose of creating and adding social value to the community of Gelvandale. Predominantly, (1) limitation of finance, (2) overwhelming effect of multiple roles, (3) negative effects of the non-accredited status of the care-giver training programme, and (4) the predominance of a destructive mindset entrenched within the Gelvandale community were key challenges he faced and attempted to deal with in setting up and operating a social venture to ultimately create social value. Although other types of data have been used, the predominant reliance on primary data collected through in-depth interviews is one of the major limitations of this qualitative study. However, this qualitative and exploratory study provides insights into our understanding of not only challenges encountered by social entrepreneurs but also the various drivers that sustain their social mission. Recommendations were then made, based on the findings from the research conducted.
Keywords: Famhealth Medipark (Port Elizabeth, -- South Africa); Businesspeople -- South Africa -- Port Elizabeth; Social entrepreneurship -- South Africa -- Port Elizabeth; Nonprofit organizations -- South Africa -- Port Elizabeth; Social responsibility of business -- South Africa -- Port Elizabeth; Community development -- South Africa -- Port Elizabeth; Social capital (Sociology) -- South Africa -- Port Elizabeth; Success in business -- South Africa -- Port Elizabeth